Risk-Return Analysis of Green Bonds Issued by Indian Corporates - Kanimozhi, V; Ramana, K (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
The world is moving towards development and this is why green finance is very important for Indias plan to have Net-Zero emissions by 2070. This study looks at how Indian companies that use green bonds to move to renewable energy are doing financially. It checks if these companies can make money compared to other companies in the market. The study looks at seven Indian companies and uses special tools like the Capital Asset Pricing Model and Sharpe Ratio to see how well they are doing. It also looks at how carbon they are not emitting and how much renewable energy they are using. This helps us see the impact of green bonds. The goal of this study is to give investors and policymakers facts to show that taking care of the environment and making money are not things in Indias modern market. Green finance and green bonds are important for Indias future. This study wants to show that they can be good for the environment and, for business.
Keywords: Green Bonds; CAPM; Nifty 50; Net-Zero 2070; Sustainable Finance; Systematic Risk; Sharpe Ratio; India